Translating political terms in China's political discourse: a critical review - Sun Aina; Ng, Chwee Fang; Subramaniam, Vijayaletchumy (Human Resource Management Academic Research Society, 2022)
There is a persistent tendency of using political terms to explain the political system and ideas in China’s political discourse. In this study, political terms refer to the professional words with specific meanings and in specific forms developed by the Communist Party of China (henceforth, CPC) and the government in a series of activities for dealing with domestic and foreign affairs. Focusing on the translation of political terms in China context, this study aims at: 1) introducing political terms in China’s political discourse, particularly the proper nouns and abbreviations, 2) critically reviewing the major studies on translating these political terms and 3) identifying some existing gaps in the current literature which need to be filled by future research. The significance of this study lies in that it contributes to a better understanding of such political terms and the status quo of their translation. Specifically, the study identifies three gaps in the current literature: a knowledge gap, or insufficiency of research on the existing defects in translating these political terms, a methodological gap, or the lack of explorations from a macroscopic translational perspective, and a theoretical gap, the scarcity of rhetorical persuasion theories as theoretical frameworks for researching the translation of such political terms. These research findings are meaningful to future scholars that would focus on the better convey of political intention expressed through political terms and the enhanced translation of China’s political discourse in international communication.